The Construction of ’Language’ as a Constitutive Meaning of Institutional Culture - JACOBS, ANTHEA H M (South African Journal of Higher Education, 2016)
This article builds on a conceptual analysis of institutional culture in higher education. A theoretical framework was proposed to analyse institutional documents of higher education institutions. One of the elements of this theoretical framework is ‘language’, by virtue of literature revealing it as a constitutive meaning of institutional culture. The aim of this article is to explore how ‘language’ as constitutive meaning of institutional culture is constructed in the institutional documents of Stellenbosch University (SU). Not only is ‘language’ a prominent news item, but it is also the subject of on-going debate at SU. My exploration is centred around two leadership eras, since there is a significant relationship between leadership and institutional culture in higher education. The findings suggest that SU has well-prepared institutional documents. The aspect of ‘language’ seems to have had a great impact on SU’s institutional culture. It features prominently in institutional documents and remains a contentious subject.